2020
DOI: 10.24018/ejbmr.2020.5.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Project Design and Sustainability of Dairy Goat Projects for Livelihood Improvement in Kenya

Abstract: The debate around sustainability of development projects is intriguing, emerging as a contemporary development paradigm. Nevertheless, empirical literature insinuates that sustainability of development projects is seldom realized. Perhaps because the sustainability drivers are not well articulated at the project design stage making sustainability uncertain. This paper calls for a decisive paradigm shift in dairy goat project designs for sustainability.  The paper is based on a study conducted in Tharaka Nithi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The study found that stakeholders included the community leaders identified in a fair process which conforms to [34] stakeholders play various roles and responsibilities in a project's delivery which is directly proportional to project outcome. Further, the study observed that it's vital to involve benefactors in the project management team and also needs assessment to be done based on community priorities which are in line with work by [35] who echoes that the voice of benefactors in the project committee is a supreme tool to successful planning and also observed by [36] that project beneficiary needs analysis is important in project beneficiary selection process. The finding also shows that traders accessed quality services at the market.…”
Section: Multiple Regression Results Of Project Design Factors and The Performance Of Green Technology Market Projectssupporting
confidence: 59%
“…The study found that stakeholders included the community leaders identified in a fair process which conforms to [34] stakeholders play various roles and responsibilities in a project's delivery which is directly proportional to project outcome. Further, the study observed that it's vital to involve benefactors in the project management team and also needs assessment to be done based on community priorities which are in line with work by [35] who echoes that the voice of benefactors in the project committee is a supreme tool to successful planning and also observed by [36] that project beneficiary needs analysis is important in project beneficiary selection process. The finding also shows that traders accessed quality services at the market.…”
Section: Multiple Regression Results Of Project Design Factors and The Performance Of Green Technology Market Projectssupporting
confidence: 59%